CHARACTERIZATION OF SAND SAMPLES FROM KARACHI BEACHES USING GAMMA SPECTROMETRY AND XRD. Issue 2 (20th March 2020) - Zeb, Jahan; Wasim, Mohammad; Shah, Sardar A; Khanam, Safia; Tahir, Hajira; Qadri, Masooda
Abstract: Chemical phase and distribution of natural radionuclides ( 226 Ra, 232 Th and 40 K) were determined for sand samples collected from ten different beaches of Karachi. All samples, except one, were identified with major and minor phases as SiO2 and CaCO3, respectively. The average activity concentrations were 24.9, 25.0 and 239 Bq kg −1 for 226 Ra, 232 Th and 40 K, respectively. Including all samples, the average radium equivalent activity was 79.1 Bq kg −1 . The external and internal radiation hazard indices and representative level index were all found below unity. The average air absorbed dose rate at 1 m above the sand due to the natural radionuclides was 18.3 nGy h −1, which was less than the world average for soil. The corresponding annual effective dose rate was 22.4 μSv y −1 . It was found that Ra eq had positive significant correlation with the amount of quartz present at the beaches.